The effect of online advertisement on young females' perception on beauty - Beh, Yin Ze; Yashinnie, Vasudevan; Jivaneswary, Ashok Kumar (2018)
Beauty has its own portrayal in advertisement nowadays. The portrayal of beauty in online advertisement may indirectly affect the young female’s perception of beauty. The perception of beauty that had been shaped may also affect their self-esteem. Hence, this study is identified the effects of online advertisement on young female’s perception of beauty. Quantitative research will be used in this study and the sampling method will be simple method sampling. This study will be targeting 200 young female students in Utar Kampar as respondent of the survey.